KEPERCAYAAN DIRI SEBAGAI PEMODERASI PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR PADA TINGKAT PEMAHAMAN AKUNTANSI - Dewi, Ni Putu Ria Arista; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
The purpose of this study is to examine self confidence as a moderating factor in the effect of emotional intelligence and learning behavior on comprehension level accounting. This study uses primary data that was collected using a questionnaire as an instrument of data collection. Respondents are students majoring in Accounting S1 Program at the Faculty of Economics and Business, University of Udayana, class of 2012. The sampling method in this research is probability sampling method with simple random technique. The number of questionnaires distributed was 207 questionnaires, while those that can be used for further analysis was 136 questionnaires. The data analysis technique used is multiple linear regression analysis and moderated regression analysis. Based on the analysis, it is found that emotional intelligence positively affects level of understanding in accounting. Learning behavior positively affect the level of understanding of accounting. Confidence moderate the impact of emotional intelligence and learning behavior on the level of understanding of accounting.
Keywords: level of accounting understand, emotional intelligence, learning behavior, confidence